Pelatihan Pembelajaran Berbasis 21st Century Skills di Sekolah Indonesia Johor Bahru Malaysia - Neneng Sri Wulan; Hafiziani Eka Putri; Puji Rahayu; Erna Suwangsih; Acep Ruswan; Srie Mulyani; D Wahyudin; Hisny Fajrussalam (Bulletin of Community Engagement, 2023)
The 21st-century skills are skills that students must master to survive and compete in this 4.0 industrial revolution era. Teachers need to have good professional competence in order to facilitate students to develop 21st-century skills. This also applies to elementary school teachers. Therefore, the teacher needs training that can provide knowledge and skills for teachers to present such learning. The training program participant is an elementary school teacher at the Indonesian School of Johor Bahru Malaysia. The problem identified is that not all SIJB's primary school teachers have diverse educational backgrounds, and the learning presented is not based on 21st-century skills. The participants of this training are 19 teachers. The program is web-based training using the ADDIE model. This training is conducted in three stages, namely the pre-implementation, implementation, and post-implementation stages. At the implementation stage, there are eight meetings containing materials on 21st Century Skills-based learning in Indonesian Language, Mathematics, Science, Social Studies and Civics, English, Arts, ICT, innovative learning models and learning life skills. Participants were given a pretest and posttest understanding of 21st Century learning. The pretest results showed an average value of 60.8, which means that participants' understanding of 21st Century learning is still quite good and the posttest average score of 84.5, which means that understanding participants is good. The result shows that the participants' understanding increased after attending the training. Based on the questionnaire results, the participant's response was quite good, and hoped that the training activities could be carried out on an ongoing basis. Keywords: 21st Century Skills Training Program, Professional Competency of Elementary Teacher